Suitability of discarded cashewnut (Anacardium occidentale) meal as replacement of soybean meal (Glycine max) in the diet of juvenile African catfish Clarias gariepinus (Burchell, 1822) - Iheanacho, Stanley; Ogueji, Emmanuel; Igberi, Christiana; Avwemoya, Fred; Amadi-Eke, Akunna; Yaji, Abubakar; Mbah, Christian (Indian Journal of Fisheries, 2019)
The search for alternative protein sources in aquaculture nutrition is still trending as the use of costly traditional feed stuffs in aquaculture diet formulation is no longer sustainable. The present study investigated the effects of partial and total dietary inclusion of cashewnut meal on growth, haematology, carcass composition, serum biochemistry and intestinal histology of juvenile African catfish Clarias gariepinus (Burchell, 1822). Soybean meal (SBM) was substituted with cashewnut meal (CM) at 0, 50 and 100% in formulated fish diets.  A total of 135 juveniles of C. gariepinus (30.25± 1.02 g; 16.08±0.34 cm) were randomly assigned to three dietary treatments (0, 50 and 100% CM based diets) at a stocking density of 45 fish per treatment and further randomised into triplicates of 15 fish per replicate. The feeding trial lasted for 56 days and fish were fed twice daily at 5% body weight. Statistical analysis was carried out for all the parameters evaluated in this study. Fish group fed 50% CM based diet had the best growth performance and haematological profile when compared to 100% CM fish group and the control group. Insignificant changes in serum biochemical parameters were observed in CM fed fish groups when compared to the control. Histological examination of fish intestinal morphology revealed no adverse changes in the cellular structure of mucosal layer and villi in 50% CM fed fish, while mild histo-morphological changes were observed in 100% CM fed fish group. Significant increases in villi length and weight were observed in fish group fed CM based diets when compared to the control. The findings of the present study revealed that partial replacement (50%) of soybean with cashewnut meal improved growth performance and haematological profile of C. gariepinus.Keywords: Anacardium occidentale, Alternative protein sources, Cashewnut meal, Clarias gariepinus, Growth metrics, Haematology, Histology, Intestine .